Gugus Konsonan (Klaster) Bahasa Sasak Dialek Ngeno-Ngene di Desa Tetebatu Selatan Kabupaten Lombok Timur - Dina Hartini; Muhammad Sukri; Rahmad Hidayat (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2024)
Consonant groups (clusters) are consonants in a row contained in one syllable. In the Sasak language, the Ngeno-ngene dialect in South Tetebatu village, there are many words that are classified as clusters, whereas in the Sasak language, the Ngeno-ngene dialect in other areas, these words are not classified as clusters. The aims of this research are (1) to determine the forms of clusters in the Sasak language, the Ngeno-ngene dialect in Tetebatu Selatan village, (2) to determine the syllabic pattern of each word that contains clusters. Data collection in this research used listening, speaking and introspection methods. The data that has been obtained will be analyzed using the intralingual matching method, the comparison technique of differentiating and comparing the main things. The results of data analysis in this research will be presented using formal and informal methods. The results of the research show that there are several forms of clusters in the Sasak language of the Ngeno-ngene dialect in South Tetebatu village such as [tr], [kl], [tl], [mb], [br], [nd], [pl], [nj ], [ŋg], [str], [pr], [bl], [jl], [bt], [nt], [bk], [bg], [mp], [sr], [ŋk], and [jd]. The syllable pattern formed from words containing consonant clusters in the Sasak language of the Ngeno-ngene dialect in South Tetebatu village is KVK-KKVK, KKVK, KKV-KVK, KKV, KKV-KV, KKV-VK, KKV-KV-KVK , KKV-KVK-KVK, KV-KVK-KKVK, KKV-KV-V, KKKVK, KKV-KV-VK, KKV-V, VK-KKVK, KKVK-KVK, KKV-KV-KV, KKV-1/2KV and KKV-KV-1/2KV.